2011
DOI: 10.1186/1752-1505-5-16
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of syphilis among demobilized child soldiers in Eastern Congo: a cross-sectional study

Abstract: BackgroundSyphilis, a known major public health issue for soldiers during periods of conflict, is exacerbated in the Democratic Republic of Congo due to widespread sexual violence. However, there has been no previous study to determine the extent of this problem. Therefore, we determined the prevalence of syphilis among young demobilized soldiers.MethodsScreening of syphilis using the rapid plasma reagin test and the Treponema pallidum hemagglutination assay was conducted in three transit sites of soldier rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Recent estimates of syphilis in child soldiers (aged <18) in the eastern Congo showed a prevalence of 3.4%, with an even distribution in men and women. 33 Additionally, estimates ranged between 0.4% and 4.0% in a recent report on river dwelling persons and internally displaced women in the eastern part of DRC. 34 However, a 2004 study of 525 women in antenatal clinics in Kinshasa (the same location as the current study) identified no active syphilis infections, and a more recent study in 2011 of women in antenatal clinics ( n = 1840) found a screening prevalence of 2.0%, suggesting that the prevalence of syphilis in women residing in Kinshasa may be very low.…”
Section: Discussionmentioning
confidence: 98%
“…Recent estimates of syphilis in child soldiers (aged <18) in the eastern Congo showed a prevalence of 3.4%, with an even distribution in men and women. 33 Additionally, estimates ranged between 0.4% and 4.0% in a recent report on river dwelling persons and internally displaced women in the eastern part of DRC. 34 However, a 2004 study of 525 women in antenatal clinics in Kinshasa (the same location as the current study) identified no active syphilis infections, and a more recent study in 2011 of women in antenatal clinics ( n = 1840) found a screening prevalence of 2.0%, suggesting that the prevalence of syphilis in women residing in Kinshasa may be very low.…”
Section: Discussionmentioning
confidence: 98%
“…Countries which border on Angola present a high rate of seroprevalence for syphilis. A study undertaken in 2011 and published in 2014 among women attending pre-natal clinics showed that the Democratic Republic of Congo presented a rate of seroprevalence of 4,2% and among demobilized soldiers it was 3, 4%, with an equal distribution in relation to sex and location [17,18]. The prevalence of syphilis observed in Zambia was 9,3% 0,4% in Botswana [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to and often interacting with psychological distress, former child soldiers often have developed serious medical conditions. Some children have had war-related injuries and disabilities, others have shown visible evidence of torture, and the occurrence of sexually transmittable diseases has generally been high (Amone P’Olak, 2009; Senga & Lutala, 2011; Wessells, 2006).…”
Section: Vulnerable and Resilient Children In A Hazardous Environmentmentioning
confidence: 99%